Analisis Optimalisasi Peningkatan Bagi Hasil Produk Mudharabah Pada PT BPRS Gebu Prima - Malau, Agus Maulana (Universitas Muhammadiyah Sumatera Utara, 2023)
results of research on the scope of the discussion regarding optimizing the increase in profit sharing for mudharabah products to increase profits and customers at PT BPRS Gebu Prima. Mudharabah contracts have a high risk because there is no mudharib obligation to repay the principal. factors that affect the determination of the profit sharing ratio for mudharabah products. Everything returns to the income earned by the BPRS and is divided based on the portion determined by BPRS Gebu Prima. in optimizing the profit sharing of mudharabah products to increase PT BPRS Gebu Prima's profits by offering these products to customers who are considered competent. In order to increase revenue, as well as rearrange the profit sharing portion that can be offered to customers, so that BPRS revenue can increase.